Pemberdayaan Keluarga dalam Penyusunan Menu MPASI Kaya Protein sebagai Strategi Pencegahan Stunting - Patiroh, Yeti; Aprilia, Yuna Trisuci; Sari, Fitria; Ambarwati, Kusmayra; Mawarni, Endang Siti; Jannah, Miftahul (Universitas Respati Indonesia, 2025)
Stunting remains a serious public health challenge in Indonesia, particularly among children under two years of age. Poor quality complementary feeding (MP-ASI), especially inadequate intake of animal protein, is a major contributing factor to stunting. This community service program aimed to empower families to understand, develop, and implement protein-rich complementary feeding menus as a strategy for preventing stunting among toddlers. The methods included interactive nutrition education, demonstrations of complementary food preparation, hands-on practice in preparing daily menus at home, and evaluation based on participant feedback and short-term post-intervention monitoring. The program involved families with children aged 6–24 months and Posyandu health cadres. The evaluation results showed that this community service activity improved participants’ knowledge and skills in selecting nutritious local food ingredients and preparing complementary foods containing animal protein sources such as eggs, fish, and chicken. Participants were also able to develop more varied daily complementary feeding menus that met toddlers’ nutritional needs. Furthermore, follow-up monitoring conducted by cadres indicated an increased frequency of animal protein use in complementary feeding and the application of weekly menus as feeding guides. Participants reported that the educational materials were easy to understand and practical for daily implementation. This program demonstrates that family empowerment through education is an effective strategy to support stunting prevention at the community level. Sustainable and collaborative program implementation involving Posyandu cadres is strongly recommended to achieve broader and long-term behavioral change.